Gugus Baru Lanskap Muslim Indonesia - M Thoyyib (Al Hikmah: Jurnal Studi Keislaman, 2018)
Abstarct. The phenomenon of the Aksi Bela Islam (ABI) shows a strong solidarity among the people. Hundreds of thousands and even millions of Muslims simultaneously went to Jakarta to demonstrate with the aim of reducing and imprisoning Governor Basuki Tjahaja Purnama (Ahok). Borrowing the term Vedi R. Hadiz, the ABI movement can be regarded as a populist Islamic movement. This paper shows that the emergence of a populist Islamic movement became a new landscape to see Indonesian Muslims. By using position warfare, the ABI movement won its victory. Therefore, to see Indonesian Muslims as a reference not only from the Nahdlatul Ulama or Muhammadiyah organizations but also from populist Islam born from the ABI.